Efeitos dos danos mecânicos e fisiológicos na colheita e beneficiamento de sementes de soja - de Mendonça Lopes, Magnólia [UNESP]; Prado, Mateus Oliveira Dedemo [UNESP]; Sader, Rubens [UNESP]; Barbosa, Rafael Marani [UNESP] (My University, 2011)
The objective of this study was to evaluate the effect of mechanical damage and physiological events in harvesting and processing of soybean cv. Mosoy RR 8000. The samples were taken during harvest manual, mechanical harvesting and during processing (receipt, pre-cleaning, cleaning, spiral separator, classification and gravity table). The physiological and physical quality was analized through the purity, germination, vigor (first germination count, seedling dry matter, accelerated aging, electrical conductivity, tetrazolium, mechanical damages and seedling field emergence) tests. The statistical design used was a entirely randomized with nine treatments (9 sampling points) with 4 replications, being the means compared by the Tuckey test at 5% probability. In the purity and seedling field emergence were observed highly significative difference between the sampling process, also this differences were obtained the first germination count, seedling dry weight matter, accelerated aging and electrical conductivity which showed smaller results for the mechanical harvesting when compared with the manual harvesting. The germination was obtained differences at 5% for the manual harvesting in relation to the mechanical harvesting were obtained smaller results, being the main cause of reducing the soybean seed quality, when compared with the manual harvesting.
Mechanical and fisiological effects on the harvesting and processing of soybean seeds
Keywords: Germination; Glycine max (L.) Merril; Injury; Tetrazolium; Viability; Vigor